Clinical and microbiological changes after minimally invasive therapeutic approaches in intrabony defects: a 12-month follow-up - Ribeiro, Fernanda V. [UNESP]; Casarin, Renato C. V. [UNESP]; Palma, Maria A. G.; Junior, Francisco H. N.; Sallum, Enilson A.; Casati, Marcio Z. (Springer, 2013)
This 12-month randomized, controlled trial evaluated the clinical effects and microbiological changes of minimally invasive nonsurgical and surgical approaches for the therapy of intrabony defects.Twenty-nine subjects with intrabony defects in single-rooted tooth were randomly assigned to; (1) minimally invasive nonsurgical technique (MINST) or (2) minimally invasive surgical technique (MIST). Quantities of Aggregatibacter actinomycetemcomitans, Tannerella forsythia, and Porphyromonas gingivalis, determined by using real-time PCR, were evaluated at baseline, 3, 6, and 12 months after the treatments. Clinical recordings-probing depth (PD), position of the gingival margin (PGM), and relative clinical attachment level (RCAL)-were obtained at baseline and 12 months post-therapy. The primary outcome variable of the study was RCAL.Both treatment modalities resulted in an improvement in all clinical recordings, with significant PD reductions (p < 0.05), RCAL gains (p < 0.05), and no change in the PGM (p > 0.05) after 12 months in both MINST and MIST groups. No clinical differences were observed between groups (p > 0.05). Regarding the microbiological outcomes, at the re-examinations, a significant decrease was observed for T. forsythia and P. gingivalis when compared with baseline (p < 0.05) for both treatments. The amount of A. actinomycetemcomitans did not reduced decrease throughout the study (p > 0.05). Intergroup differences in the microbiological assay were not found at any time point (p > 0.05).Both MINST and MIST provided comparable clinical results and microbiological changes in the treatment of intrabony defects over 12 months follow-up.This randomized, controlled, parallel trial revealed that both therapeutic modalities may promote clinical and microbiological benefits at 12 months post-therapy.
Keywords: Microbiology; Periodontitis; Microsurgery; Surgical procedures; Minimally invasive; Root planing